Enantioseparation of racemic compounds in reserved phase liquid chromatography using cationic β-cyclodextrin as chiral stationary phase. - Khoo, Linda Wei Ling. (2009)
Two novel chiral stationary phases (CSP 1: dimethylbutadiene and CSP 2: methylmethacylate cationic phenylcarbamated-β-cyclodextrin) (Figure 1) were developed and immobilized at the C-6 position of cyclodextrin ring via polymerization. This positively charged imidazole was used to elucidate the influence of additional electrostatic interaction on enantioseparation for ionzible acidic compounds with carboxyl COOH group. Chromatographic methods were developed to evaluate its chiral discrimination ability towards acidic, basic and neutral racemates. The influence of varied methanol composition, pH and concentration of triethylammonium acetate (TEAA) on retention, selectivity and resolution were investigated. The CSP 1 has demonstrated enantioseparation for Fenoterol. The CSP 2 has been successful in separating Flavanones, Dobutamine, Atropines, and Etilefrin with Fenoterol which was not previously reported in reverse phase HPLC separation. Fenoterol (α = 2.4, Rs = 2.8) and Atropine (α = 1.5, Rs = 2.5) were based line separated and modest resolution was obtained for flavanones under methanol/buffer (0.16% w/v TEAA, pH 5.2). The column does not display chiral recognition for non-steroidal anti-inflammatory drugs: profen. These results indicate the dependence of the types of substituted group on the phenylcarbamate on enantioseparation. TEAA addictive was found to reduce peak width and enhance the resolution of separated peaks. The retention and selectivity decreases with increase in methanol concentration. pH was found to influence basic and acidic compounds to different extent but has no influence on neutral compounds.